2013
DOI: 10.4137/bcbcr.s12214
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptors and Age Distribution in Breast Cancer Patients at a University Hospital in Northern Egypt

Abstract: Introduction:Breast cancer is the most common cancer among Egyptian women. The disease is often advanced at diagnosis. Since molecular profiling is not feasible in routine practice, we sought to examine the association of age distribution with hormone receptor profile, disease stage and outcome among Egyptian women.Patients and methods:We conducted a retrospective review of breast cancer patients treated at Mansoura University Cancer Center in the Nile Delta from 2006 through 2011. Age groups were examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…The incidence of Her2 positive tumors in the current study was 28.5% but this figure has to take into consideration that our institute is a referral center for the targeted therapy trastuzumab so though our results were in accordance with Salhia et al [21] who reported on an incidence of 25.1%, it was different from Hussein et al who reported on an incidence as low as 14.1% [20].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The incidence of Her2 positive tumors in the current study was 28.5% but this figure has to take into consideration that our institute is a referral center for the targeted therapy trastuzumab so though our results were in accordance with Salhia et al [21] who reported on an incidence of 25.1%, it was different from Hussein et al who reported on an incidence as low as 14.1% [20].…”
Section: Discussionsupporting
confidence: 65%
“…In the current study there was a statistically significant difference in distribution of molecular subtypes by age (P-value: 0.031), so though Hormonal positive tumors (luminal subtype) in general was the predominant subtype among all age groups, HR+/Her+ were higher in the younger age group (27% compared to 17.2%) and Her2 overexpression subtype was higher in the younger age group (17.6% compared to 8.2%). Triple negative tumors had the incidence of 16.7% in the current study compared to 19.0% reported by Hussein et al [20], and 28.5% in a report of Elhawary et al who reported on 274 surgical specimens [28]. High frequency of the basal-like subtype has been reported in about 40% of young premenopausal African North American women [29].…”
Section: Discussioncontrasting
confidence: 49%
“…The mean age at diagnosis in our study was 47.5 years which is very similar to that reported in other Asian studies. However, in western population the mean age at diagnosis, as published by Surveillance, Epidemiology and End results (SEER) is 61 years (Hussein O et al, 2013). Majority of our patients presented with nodal involvement, larger tumor size and receptor (ER and PR) positivity.…”
Section: Discussionmentioning
confidence: 79%
“…*These studies provided only a combined HR estimate for tumors that were either ER+ or PR+ [33] or ER+ and/or PR+ ([29]; [43]; [52]; [63]; [64]; [71]). These HR estimates were included in both the ER+ and PR+ plots.…”
Section: Resultsmentioning
confidence: 99%